Gender differences in lifetime and current use of online support for recovery from alcohol use disorder. (19th June 2022) - Gilbert, Paul A.; Saathoff, Elizabeth; Russell, Alex M.; Brown, Grant
Abstract: Background: Digital recovery support services (D‐RSS) use technology to engage individuals seeking recovery from alcohol use disorder (AUD). Given sparse data on use of these emergent services as well as longstanding and stark gender disparities in use of traditional alcohol treatment services, we sought to quantify lifetime and current D‐RSS use and to test associations with several recovery outcomes, with particular attention to gender differences. Methods: We analyzed data obtained in fall 2020 in a national survey of adults with a resolved alcohol problem ( n  = 1487). We estimated lifetime and current D‐RSS use, prevalence of various types of D‐RSS, and related outcomes (e.g., recovery stability, relapse events, quality of life). Stratified logistic regression models identified correlates of D‐RSS use for women and men, controlling for demographic and AUD characteristics. Results: Overall, an estimated 14.9% of the population of adults with a resolved alcohol problem reported lifetime use of D‐RSS, with no difference by gender. Current use was lower and was reported by more men than women (9.9% vs. 5.8%, respectively). Men had higher odds of D‐RSS use if they had <1 year of recovery (adjusted odds ratio [aOR] 7.84), 1 to 5 years of recovery (aOR 2.17), and if never married (aOR 3.29). Among women, higher odds of D‐RSS were associated with AUD symptom count (aOR 1.30), being unemployed (aOR 9.85), and having minor children in the household (aOR 3.58). Among women, there was no association between D‐RSS use and recovery stability, relapse events, and quality of life. However, among men D‐RSS use was associated with reporting that the COVID‐19 pandemic had made it more difficult to resist alcohol or drugs and with lower self‐reported quality of life. Conclusions: D‐RSS are a promising technological approach to support recovery. There is room to increase their use, and gender‐specific approaches may be needed given different correlates of use for women and men. In addition, further research is needed to explore whether D‐RSS may confer benefits through similar mechanisms as in‐person recovery services. Abstract : Digital recovery support services, such as discussion boards and chat rooms, online mutual‐help group meetings, and social networking sites, may provide a novel means to engage individuals seeking recovery from alcohol use disorders, thereby addressing the large unmet need for services. Our study found low levels of lifetime use as well as different correlates of current use for women versus men. There is potential to increase use of digital recovery support services, however, tailored gender‐specific interventions may be needed.